Examining the Occupational Health Risks and Socioeconomic Challenges Faced by Sanitation Workers in Urban Slums - Ngatia, Alex; Anciano, Fiona; Kagendo, Dorothy; Riungu, Joy (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Sanitation workers play a critical role in global health, yet they often face neglect, especially in in informal settlements. This study investigates the occupational safety, health, and dignity (OSH&D) sanitation workers in Mukuru kwa Reuben slums, Nairobi, Kenya, focusing on those involved in faecal sludge management. Employing a mixed methods approach with 40 workers, the research reveals alarming occupational hazards: chemical exposure (40%), psychosocial issues (27.5%), physical injuries (22.5%), and biological risks (10%). Socioeconomic factors, such as low income and limited education, exacerbate these vulnerabilities. The study highlights a critical lack of (OSH&D) protections: 85% lack personal protective equipment (PPE), and 72.5% lack essential training. Furthermore, 67.5% face cultural stigma and discrimination, and lack legal protection. Statistically significant correlations demonstrate the negative impact of poverty (r = -0.491, p = 0.000) and environmental hazards (r = 0.672, p = 0.000) on (OSH&D). Conversely, a positive correlation exists between income and OSH&D (r = 0.613, p = 0.000). These findings underscore the need for comprehensive policy reforms to improve legal protections, increase income, and enhance training and equipment availability. This will significantly improve the dignity and safety of sanitation workers. Future research should focus on longitudinal studies and intervention evaluations to further understand and mitigate these challenges.